The Characteristics of the North Sea and Its Importance for Maritime Transport: Array - Chirosca, Ana-Maria; Liliana Rusu, Liliana (Acta Universitatis Danubius. Œconomica, 2021)
The North Sea is one of the largest seas in Europe in terms of maritime traffic. It is positioned between Norway, England, France, Germany and Denmark, a position that positively favours the maritime sector and the energy sector. Also, the North Sea area is a rich and important natural area for fishing. Due to the exchange of water with the Atlantic Ocean and the Baltic Sea, this sea is constantly changing and developing a complex ecosystem, which scientists are constantly studying to understand. The energetic potential places the North Sea on the first position in the European seas, and because of this in this area they are found in most wind turbines, in proportion of 70%. In this paper, a study was performed on the characteristics of the North Sea and maritime traffic in this area, as well as the exploitation potential both in terms of oil and wind turbines. The wind and wave conditions for the last twenty years, based on ERA5 data, from the Copernicus Climate Change Service (C3S) were also studied.